Sustainability gaps in municipal solid waste management: The case of landfills - Stefan Bayer; Jacques Méry (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2006)
Our paper compares external effects of two municipal solid waste disposal technologies, bioreactor and dry tomb landfills, in a 600-year time-horizon using two different discounting techniques: Constant conventional discounting and Generation Adjusted Discounting (GAD). The paper starts with a short description of the basic characteristics of the two landfill-types. To demonstrate the sustainability deficiencies of constant discounting sustainability gaps are defined and calculated. Reference case for these calculations is the GAD which takes into account the basic requirements of sustainable development, namely intergenerational equity. Our calculations show that constant discounting usually uses too high discount rates to be in accordance with fundamental sustainability criteria leading to biased political suggestions. However, our approach is not solely restricted to landfills. It could be used as a guide to quickly check whether the results of social cost-benefit analyses of long-term public projects are in accordance with fundamental sustainability criteria.
urn:nbn:de:gbv:705-opus-16939
Keywords: 330; Generation Adjusted Discounting (GAD); constant discounting; sustainability gap; external costs; bioreactor landfill; dry tomb landfill